(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the impact of smoking combined with natural spices (salt, clove, garlic, and ginger) on the nutritional value and profitability of Clarias gariepinus and Oreochromis niloticus. The fish samples undergo hot smoking after treatment with the spices, and data were analyzed using one-way ANOVA at a significance level of p<0.05. Result from proximate composition of Clarias gariepinus showed a moisture range of 4.59-57.20%, ash 7.32-16.08%, fat 7.61-13.94%, crude protein 25.72-53.13%, nitrogen-free extract 2.15-17.26%, and dry matter 42.80-95.41%. Similarly, the result obtained from Oreochromis niloticus showed a moisture range of 3.57-55.5%, ash 9.39-17.96%, fat 6.30-10.27%, crude protein 24.62-49.25%, nitrogen-free extract 5.14-23.46%, and dry matter 44.50-96.43%. The profitability results of Clarias gariepinus and Oreochromis niloticus indicated the total variable cost of production for all items incurred is ₦13,650 and ₦10,650, respectively. The total revenue generated per 1 kg of smoked Clarias gariepinus ranges from ₦10,000-₦10,630 (T1-T4), while ₦7,500-₦8,050 (T1-T4) were generated from the price of smoked Oreochromis niloticus. The benefit cost ratio (BCR) obtained from the treatment was 3.278 T1, 2.912 T2, 3.156 T3, 3.181 T4, and T1 ₦3.260, T2 ₦2.775, T3 ₦3.128, T4 ₦3.163. Return on investment (ROI) for Clarias gariepinus ranges from ₦1.912-₦2.278 per ₦1 invested, whereas for Oreochromis niloticus it was ₦1.775-₦2.260 per ₦1 invested, respectively. Conclusively, incorporating spices before smoking enhances both the nutritional quality and profitability of Clarias gariepinus and Oreochromis niloticus. While salt yielded the highest profit, ginger and garlic offered better nutrient profiles.